The production of glycoproteins by transient expression in Mammalian cells. - Nettleship, J; Rahman-Huq, N; Owens, R (2009)
In this chapter, protocols for the growth and transfection of Human Embryonic Kidney (HEK) 293T cells for small scale expression screening and large scale protein production are described. Transient expression in mammalian cells offers a method of rapidly producing glycoproteins with a relatively high throughput. HEK 293T cells, in particular, can be transfected with high efficiency (> 50% cell expression) and are amenable to culture at multi-litre scale. Growing cells in micro-plate format allows screening of large numbers of vectors in parallel to prioritise those amenable to scale-up and purification for subsequent structural or functional studies. The glycoform of the expressed protein can be modified by treating cell cultures with kifunensine which inhibits glycan processing during protein synthesis. This results in the production of a chemically homogeneous glycoprotein with short mannose-rich sugar chains attached to the protein backbone. If required, these can be readily removed by endoglycosidase treatment.